Release of β-casomorphin-7 in A1/A1 and A2/A2 dairy systems: Insights from simulated semi-dynamic gastrointestinal digestion - Davor Daniloski; Noel A. McCarthy; Todor Vasiljevic; Neha Sharma; Conor J. Fitzpatrick; André Brodkorb; Thao T. Le; Lotte J. Knudsen; Lotte B. Larsen; Nina A. Poulsen (Food Chemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The challenge of reducing antimicrobial resistance (AMR) across the one health landscape: Diverse perspectives on AMR risks and their mitigation in sinks, drains, and wastewater - Hillary A. Craddock; Aoife Kearney; Fidelma Fitzpatrick; Caoimhe Finn; Mary T. Pryce; Deirdre Fitzgerald-Hughes (Science of The Total Environment, 2025)

Spatial Replication Is Important for Developing Landscape Genetic Inferences for a Wetland Salamander - Bryce S. Wade; Todd W. Pierson; Benjamin M. Fitzpatrick; Evin T. Carter (Molecular Ecology, 2025)
Habitat fragmentation is a pressing threat to wildlife populations, and maintenance of gene flow between populations is an essential goal of conservation. Resistance surfaces have emerged as an important tool for modelling connectivity and developing management strategies to mitigate effects of habitat fragmentation. However, recent studies have noted inconsistencies in the factors most strongly associated with connectivity across different landscapes. Thus, replication of genetic‐based resistance surface optimisation across landscapes may be necessary for making robust conclusions about the influence of environmental variables. Accordingly, replication represents a substantive challenge and opportunity in the field of landscape genetics. In this study, we conducted replicated landscape genetic analyses across five landscapes in Tennessee and Kentucky for a threatened wetland amphibian, the four‐toed salamander ( Hemidactylium scutatum ). We tested multiple hypotheses of how different landscape features that could directly affect small, desiccation‐intolerant amphibians (e.g., canopy cover) influenced gene flow and assessed the appropriate scale at which to model different features. We found some concordance in the landscape features that influenced gene flow (e.g., a common importance of forest cover and topography), but also some differences—potentially owing to the difference in variability of predictors across landscapes. We also found discordance in the scale of effect of different features across landscapes. Our work emphasises that flat areas of moist forest not bisected by roads may be important for H. scutatum conservation, and our replicated design allows us to identify relationships that would have been missed if only using one study site.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Inpatient referrals to a specialist falls and syncope service: prevalence of STOPPFall FRIDs and review of deprescribing patterns - D. O’Donnell; T. Zainal; K. Malomo; N. Fitzpatrick; C. Rice; L. Byrne; R. Briggs; C. Cunningham; R. A. Kenny; A. H. Lavan (European Journal of Clinical Pharmacology, 2025)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Equivalent roles of marine subsidies and island characteristics in shaping island bird communities - Debora S. Obrist; Patrick J. Hanly; Jeremiah C. Kennedy; Owen T. Fitzpatrick; Sara B. Wickham; Wiebe Nijland; Luba Y. Reshitnyk; Chris T. Darimont; Brian M. Starzomski; John D. Reynolds (Journal of Biogeography, 2024)
Aim Species distributions across islands are shaped by dispersal limitations, environmental filters and biotic interactions but the relative influence of each of these processes has rarely been assessed. Here, we examine the relative contributions of island characteristics, marine subsidies, species traits, and species interactions on avian community composition. Location Central Coast region of British Columbia, Canada. Taxon Terrestrial breeding birds. Methods We observed 3610 individuals of 32 bird species on 89 islands that spanned multiple orders of magnitude in area (0.0002–3 km 2 ). We fit a spatially explicit joint species distribution model to estimate the relative contributions of island physical characteristics, island‐specific inputs of marine subsidies, species' traits, and biotic interactions on species distributions. Biogeographic characteristics included island area, isolation, and habitat heterogeneity, while marine influence was represented by forest‐edge soil δ 15 N, wrack biomass, shoreline substrate, and distance to shore. This approach also allowed us to estimate how much variation in distributions resulted from species' biological traits (i.e. body mass, feeding guild, feeding height, and nesting height). Results Bird species distributions were determined almost equivalently by island biogeographic characteristics (23.5% of variation explained) and marine influence (24.8%). We detected variation in species‐specific responses to both island biogeographic characteristics and marine influence, but no significant effect of any biological trait examined. Additionally, we found evidence that habitat preferences were a more important driver than competitive interactions. Main Conclusions Although most island biogeographic studies focus only on islands' physical characteristics, we found evidence for an equivalent role of marine subsidy in structuring island bird communities. Our study suggests that for small islands, disentangling the effects of island biogeographic characteristics, marine inputs, and biotic interactions is a useful next step in understanding species distributions.

Terrestrial carbon isotope stratigraphy of the Eocene–Oligocene transition, Petrockstowe and Bovey basins, Devon, UK - Mohammed S. Chaanda; Stephen T. Grimes; Rhodri M. Jerrett; Mark Anderson; Melanie J. Leng; Meriel E. Fitzpatrick; Gregory D. Price (Proceedings of the Geologists' Association, 2023)

Parallel evaluation of alternative skin barrier models and excised human skin for dermal absorption studies in vitro - Alec T. Salminen; Kelly J. Davis; Robert P. Felton; Nathania Nischal; Linda S. VonTungeln; Frederick A. Beland; Kristy Derr; Paul C. Brown; Marc Ferrer; Linda M. Katz; Nicole C. Kleinstreuer; Jonathan Leshin; et al. (Toxicology in Vitro, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2022)

Behavioral Interactions between a Native and an Invasive Fish Species in a Thermally Heterogeneous Experimental Chamber - Lindsy R. Ciepiela; Ryan M. Fitzpatrick; Samuel T. Lewis; Yoichiro Kanno (Fishes, 2021)
Mechanisms of the displacement of native fish by nonnative fish can include agonistic behaviors that push native fish species out of their preferred habitat, including their thermal optima. To examine these interactions, we built an experimental thermal preference chamber to evaluate: (1) the thermal preference of native, glacial relict northern redbelly dace Chrosomus eos; (2) if the thermal preference and movement changed in the presence of the invasive western mosquitofish Gambusia affinis; and (3) the direction of agonistic interactions. We hypothesized that G. affinis would express agonistic behavior toward C. eos, because G. affinis is widely recognized as an aggressive invader. Given the temperature range of the experimental chamber, i.e., 20–30 °C, C. eos selected an average of 24.3 °C as its thermal preference. After G. affinis’ introduction, the thermal preference of C. eos increased by 1.7 °C and the movement, given by distance (cm) travelled, increased by 21%. Contrary to our prediction, more agonistic interactions were observed in C. eos toward G. affinis. These results indicate that agonistic behavior of G. affinis toward native fish species may be species- and condition-specific, and may not always be the primary mechanism of native species’ displacement. Biological invasions are a global issue and altered thermal regimes are expected to continue. This study provided the novel approach using of a thermally heterogeneous thermal chamber to examine thermal preferences and aggressive interactions between a native and an invasive species. Future research should examine other life history traits that may be conveying the competitive advantage to G. affinis.

Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2021)

Can indicator species guide conservation investments to restore connectivity in Great Lakes tributaries? - Kimberly B. Fitzpatrick; Allison T. Moody; Austin Milt; Matthew E. Herbert; Mary Khoury; Eugene Yacobson; Jared A. Ross; Patrick J. Doran; Michael C. Ferris; Peter B. McIntyre; Thomas M. Neeson (Biodiversity and Conservation, 2021)

Snowpack, Tree Size, and Ecological Legacies Promote Seedling Establishment in Tree Islands at the Treeline - O. T. Fitzpatrick; M. Blade; L. A. Fishback; G. P. Kershaw; J. Muffly; S. D. Mamet (Ecosystems, 2020)

Temperature and telomeres: thermal treatment influences telomere dynamics through a complex interplay of cellular processes in a cold-climate skink - L. J. Fitzpatrick; M. Olsson; L. M. Parsley; A. Pauliny; T. L. Pinfold; T. Pirtle; G. M. While; E. Wapstra (Oecologia, 2019)

Development and Implementation of a Continuing Medical Education Program in Canada: Knowledge Translation for Renal Cell Carcinoma (KT4RCC) - Luke T. Lavallée; Ryan Fitzpatrick; Lori A. Wood; Joan Basiuk; Christopher Knee; Sonya Cnossen; Ranjeeta Mallick; Kelsey Witiuk; Marie Vanhuyse; Simon Tanguay; Antonio Finelli; Michael A. S. Jewett; et al. (Journal of Cancer Education, 2019)

Conserving rare species can have high opportunity costs for common species - Thomas M. Neeson; Patrick J. Doran; Michael C. Ferris; Kimberly B. Fitzpatrick; Matthew Herbert; Mary Khoury; Allison T. Moody; Jared Ross; Eugene Yacobson; Peter B. McIntyre (Global Change Biology, 2018)
Conservation practitioners face difficult choices in apportioning limited resources between rare species (to ensure their existence) and common species (to ensure their abundance and ecosystem contributions). We quantified the opportunity costs of conserving rare species of migratory fishes in the context of removing dams and retrofitting road culverts across 1,883 tributaries of the North American Great Lakes. Our optimization models show that maximizing total habitat gains across species can be very efficient in terms of benefits achieved per dollar spent, but disproportionately benefits common species. Conservation approaches that target rare species, or that ensure some benefits for every species (i.e., complementarity) enable strategic allocation of resources among species but reduce aggregate habitat gains. Thus, small habitat gains for the rarest species necessarily come at the expense of more than 20 times as much habitat for common ones. These opportunity costs are likely to occur in many ecosystems because range limits and conservation costs often vary widely among species. Given that common species worldwide are declining more rapidly than rare ones within major taxa, our findings provide incentive for triage among multiple worthy conservation targets.

The interplay of climate and land use change affects the distribution of EU bumblebees - Leon Marshall; Jacobus C. Biesmeijer; Pierre Rasmont; Nicolas J. Vereecken; Libor Dvorak; Una Fitzpatrick; Frédéric Francis; Johann Neumayer; Frode Ødegaard; Juho P. T. Paukkunen; Tadeusz Pawlikowski; Menno Reemer; et al. (Global Change Biology, 2018)
Bumblebees in Europe have been in steady decline since the 1900s. This decline is expected to continue with climate change as the main driver. However, at the local scale, land use and land cover ( LULC ) change strongly affects the occurrence of bumblebees. At present, LULC change is rarely included in models of future distributions of species. This study's objective is to compare the roles of dynamic LULC change and climate change on the projected distribution patterns of 48 European bumblebee species for three change scenarios until 2100 at the scales of Europe, and Belgium, Netherlands and Luxembourg ( BENELUX ). We compared three types of models: (1) only climate covariates, (2) climate and static LULC covariates and (3) climate and dynamic LULC covariates. The climate and LULC change scenarios used in the models include, extreme growth applied strategy ( GRAS ), business as might be usual and sustainable European development goals. We analysed model performance, range gain/loss and the shift in range limits for all bumblebees. Overall, model performance improved with the introduction of LULC covariates. Dynamic models projected less range loss and gain than climate‐only projections, and greater range loss and gain than static models. Overall, there is considerable variation in species responses and effects were most pronounced at the BENELUX scale. The majority of species were predicted to lose considerable range, particularly under the extreme growth scenario ( GRAS ; overall mean: 64% ± 34). Model simulations project a number of local extinctions and considerable range loss at the BENELUX scale (overall mean: 56% ± 39). Therefore, we recommend species‐specific modelling to understand how LULC and climate interact in future modelling. The efficacy of dynamic LULC change should improve with higher thematic and spatial resolution. Nevertheless, current broad scale representations of change in major land use classes impact modelled future distribution patterns.

Theory of Visual Attention (TVA) applied to mice in the 5-choice serial reaction time task - C. M. Fitzpatrick; M. Caballero-Puntiverio; U. Gether; T. Habekost; C. Bundesen; S. Vangkilde; D. P. D. Woldbye; J. T. Andreasen; A. Petersen (Psychopharmacology, 2017)

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

Fifty years of co‐evolution and beyond: integrating co‐evolution from molecules to species - Diego Carmona; Connor R. Fitzpatrick; Marc T. J. Johnson (Molecular Ecology, 2015)
Fifty years after Ehrlich and Raven's seminal paper, the idea of co‐evolution continues to grow as a key concept in our understanding of organic evolution. This concept has not only provided a compelling synthesis between evolutionary biology and community ecology, but has also inspired research that extends beyond its original scope. In this article, we identify unresolved questions about the co‐evolutionary process and advocate for the integration of co‐evolutionary research from molecular to interspecific interactions. We address two basic questions: (i) What is co‐evolution and how common is it? (ii) What is the unit of co‐evolution? Both questions aim to explore the heart of the co‐evolutionary process. Despite the claim that co‐evolution is ubiquitous, we argue that there is in fact little evidence to support the view that reciprocal natural selection and coadaptation are common in nature. We also challenge the traditional view that co‐evolution only occurs between traits of interacting species. Co‐evolution has the potential to explain evolutionary processes and patterns that result from intra‐ and intermolecular biochemical interactions within cells, intergenomic interactions (e.g. nuclear‐cytoplasmic) within species, as well as intergenomic interactions mediated by phenotypic traits between species. Research that bridges across these levels of organization will help to advance our understanding of the importance of the co‐evolutionary processes in shaping the diversity of life on Earth.

The importance of plant genotype and contemporary evolution for terrestrial ecosystem processes - Connor R. Fitzpatrick; Anurag A. Agrawal; Nathan Basiliko; Amy P. Hastings; Marney E. Isaac; Michael Preston; Marc T. J. Johnson (Ecology, 2015)
Plant genetic variation and evolutionary dynamics are predicted to impact ecosystem processes but these effects are poorly understood. Here we test the hypothesis that plant genotype and contemporary evolution influence the flux of energy and nutrients through soil, which then feedback to affect seedling performance in subsequent generations. We conducted a multiyear field evolution experiment using the native biennial plant Oenothera biennis . This experiment was coupled with experimental assays to address our hypothesis and quantify the relative importance of evolutionary and ecological factors on multiple ecosystem processes. Plant genotype, contemporary evolution, spatial variation, and herbivory affected ecosystem processes (e.g., leaf decay, soil respiration, seedling performance, N cycling), but their relative importance varied between specific ecosystem variables. Insect herbivory and evolution also contributed to a feedback that affected seedling biomass of O. biennis in the next generation. Our results show that heritable variation among plant genotypes can be an important factor affecting local ecosystem processes, and while effects of contemporary evolution were detectable and sometimes strong, they were often contingent on other ecological factors.

The synthetic triterpenoid (CDDO-Im) inhibits STAT3, as well as IL-17, and improves DSS-induced colitis in mice - Leo R. Fitzpatrick; Elizabeth Stonesifer; Jeffrey S. Small; Karen T. Liby (Inflammopharmacology, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Assessing the potential for post‐copulatory sexual selection in elasmobranchs - J. L. Fitzpatrick; R. M. Kempster; T. S. Daly‐Engel; S. P. Collin; J. P. Evans (Journal of Fish Biology, 2012)
This review highlights the potential role that post‐copulatory sexual selection plays in elasmobranch reproductive systems and the utility of this group to further understanding of evolutionary responses to the post‐copulatory processes of sperm competition and cryptic female choice. The growing genetic evidence for female multiple mating (polyandry) in elasmobranchs is summarized. While polyandry appears to be common in this group, rates of multiple paternity are highly variable between species suggesting that there is large variance in the strength of post‐copulatory sexual selection among elasmobranchs. Possible adaptations of traits important for post‐copulatory sexual selection are then considered. Particular emphasis is devoted to explore the potential for sperm competition and cryptic female choice to influence the evolution of testes size, sperm morphology, genital morphology and sperm storage organs. Finally, it is argued that future work should take advantage of the wealth of information on these reproductive traits already available in elasmobranchs to gain a better understanding of how post‐copulatory sexual selection operates in this group.

Analysis of genetic diversity in flowering dogwood natural stands using microsatellites: the effects of dogwood anthracnose - D. Hadziabdic; B. M. Fitzpatrick; X. Wang; P. A. Wadl; T. A. Rinehart; B. H. Ownley; M. T. Windham; R. N. Trigiano (Genetica, 2010)

Characterisation of microsatellite loci in the groundwater amphipod Chydaekata sp. (Malacostraca: Paramelitidae) - T. L. Finston; S. S. Lukehurst; G. L. Fitzpatrick (Conservation Genetics Resources, 2010)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Recent divergence with gene flow in Tennessee cave salamanders (Plethodontidae: Gyrinophilus ) inferred from gene genealogies - MATTHEW L. NIEMILLER; BENJAMIN M. FITZPATRICK; BRIAN T. MILLER (Molecular Ecology, 2008)
Cave organisms occupy a special place in evolutionary biology because convergent morphologies of many species demonstrate repeatability in evolution even as they obscure phylogenetic relationships. The origin of specialized cave‐dwelling species also raises the issue of the relative importance of isolation vs. natural selection in speciation. Two alternative hypotheses describe the origin of subterranean species. The ‘climate‐relict’ model proposes allopatric speciation after populations of cold‐adapted species become stranded in caves due to climate change. The ‘adaptive‐shift’ model proposes parapatric speciation driven by divergent selection between subterranean and surface habitats. Our study of the Tennessee cave salamander complex shows that the three nominal forms ( Gyrinophilus palleucus palleucus , G. p. necturoides , and G. gulolineatus ) arose recently and are genealogically nested within the epigean (surface‐dwelling) species, G. porphyriticus . Short branch lengths and discordant gene trees were consistent with a complex history involving gene flow between diverging forms. Results of coalescent‐based analysis of the distribution of haplotypes among groups reject the allopatric speciation model and support continuous or recurrent genetic exchange during divergence. These results strongly favour the hypothesis that Tennessee cave salamanders originated from spring salamanders via divergence with gene flow.

Anthropogenic impacts to coral reefs in Palau, western Micronesia during the Late Holocene - S. M. Fitzpatrick; T. J. Donaldson (Coral Reefs, 2007)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Differentiation-induced HL-60 cell apoptosis: A mechanism independent of mitochondrial disruption? - B. T. Doyle; A. J. O’Neill; J. M. Fitzpatrick; R. W. G. Watson (Apoptosis, 2004)

Modifications of the comprehensive method for total glycoalkaloid determination - T. J. Fitzpatrick; J. D. Mackenzie; P. Gregory (American Journal of Potato Research, 1978)

Potato glycoalkaloids: Increases and variations of ratios in aged slices over prolonged storage - T. J. Fitzpatrick; S. F. Herb; S. F. Osman; J. A. McDermott (American Journal of Potato Research, 1977)

A comprehensive method for the determination of total potato glycoalkaloids - T. J. Fitzpatrick; S. F. Osman (American Journal of Potato Research, 1974)

Selection potential for tuber total nitrogen and total solids content in a tetraploid breeding population - L. L. Sanford; T. J. Fitzpatrick; W. L. Porter (American Journal of Potato Research, 1971)

Protein, nonprotein, and total nitrogen in seedlings of potatoes - T. J. Fitzpatrick; R. V. Akeley; J. W. White; W. L. Porter (American Journal of Potato Research, 1969)

Continued studies of the relationship of specific gravity to total solids of potatoes - T. J. Fitzpatrick; W. L. Porter; G. V. C. Houghland (American Journal of Potato Research, 1969)

Studies of the relationship of specific gravity to total solids of potatoes - W. L. Porter; T. J. Fitzpatrick; E. A. Talley (American Journal of Potato Research, 1964)